GOVERNMENT OFFICERS WITH WORK AGREEMENTS: LEGAL PROTECTION MEASURES AGAINST TERMINATION OF EMPLOYMENT BY THE GOVERNMENT - Firna Novi Anggoro (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The presence of PPPK is expected to become professional employees who are recruited as collaborative and competitive partners who occupy similar positions in the civil bureaucracy, but unfortunately, the Undang-Undang No. 5 Tahun 2014 regarding the State Civil Apparatus and the Peraturan Pemerintah No. 49 Tahun 2018 on the management of PPPK still weakens the position of the PPPK in terms of working relations with the government (the agency that employs the PPPK) so that it is prone to abuse of authority and arbitrary actions by the government (the agency providing the PPPK) to terminate the PPPK employment relationship, such as the reason for a serious violation of the PPPK discipline, not achieving performance targets, as well as adjustments to agency needs. These various problems need to be anticipated, considering that the sustainability of the problem of PPPK that is disadvantaged due to PHPK can hinder the achievement of bureaucratic reform programs, especially related to efforts to realize a merit system in ASN management. This study will discuss how to protect the PPPK who was harmed by the decision of the Civil Service Supervisor because it was carried out by PHPK. The research method used is a normative juridical method with the problem approach used is a statutory approach and a conceptual approach. Base on the Undang-Undang No. 5 Tahun 2014 regarding the State Civil Apparatus and the Peraturan Pemerintah Nomor 79 Tahun 2021, the PPPK can make administrative efforts, namely administrative appeals submitted to the ASN Advisory Board (BPASN). If the PPPK is still dissatisfied with the BPASN's decision, the PPPK can file a legal action through the State Administrative High Court.